The cortical microstructural basis of lateralized cognition: a review - Chance, Steven A. (Frontiers in Psychology, 2014)
The presence of asymmetry in the human cerebral hemispheres is detectable at both the macroscopic and microscopic scales. The expansion of cortical surface during development and across evolutionary time is largely due to the proliferation and spacing of the microscopic vertical columns of cells that form the cortex. In the asymmetric planum temporale, minicolumn width asymmetry is associated with surface area asymmetry. This asymmetry of minicolumn spacing is absent in the equivalent areas of the brains of other apes. The left hemisphere dominance for speech depends, partly, on a bias for higher resolution processing across widely spaced minicolumns with less overlapping dendritic fields, whereas narrow minicolumn spacing in the right hemisphere is associated with overlapping, low resolution, holistic processing. This concept refines the simple notion that a larger brain area is associated with dominance for a function with a mechanistic explanation associated with ‘processing type’. Face processing provides a test case - it is the opposite of language, being dominant in the right hemisphere. Consistent with the bias for holistic, configural processing of faces, the minicolumns in the right hemisphere fusiform gyrus are narrower than in the left hemisphere, which is associated with featural processing. Again, this asymmetry is not found in chimpanzees. The difference between hemispheres may also be seen in terms of processing speed, facilitated by asymmetric myelination of white matter tracts. By cross-referencing the differences between the active fields of the two hemispheres, via tracts such as the corpus callous, the relationship of local features to global features may be encoded. Altered minicolumn organisation is also observed in neuropsychiatric disorders such as autism and schizophrenia. This may be a consequence of disequilibrium in the processing of local and global features related to disorganisation of asymmetric minicolumnar units o